Desmoglein-2 modulates tumor progression and osimertinib drug resistance through the EGFR/Src/PAK1 pathway in lung adenocarcinoma. (28th July 2020) - Jin, Runsen; Wang, Xinfeng; Zang, Ruochuan; Liu, Chengming; Zheng, Sufei; Li, Hecheng; Sun, Nan; He, Jie
Abstract: Desmoglein-2 (DSG2), a member of the cadherin superfamily, has been implicated in cell-cell adhesion and tumorigenesis. Here, we demonstrate that high DSG2 expression in both lung adenocarcinoma (LUAD) cell lines and tissues is associated with poor prognosis in LUAD patients. Notably, DSG2 overexpression promoted cell proliferation and migration, and increased resistance to the EGFR tyrosine kinase inhibitor osimertinib, whereas DSG2 silencing could reverse these results. Moreover, direct interaction between DSG2 and EGFR in the cell membrane stimulated EGFR signaling to promote tumorigenesis, and loss of DSG2 resulted in EGFR translocation into the cytoplasm. In addition, DSG2 was required for EGFR binding to Src; consequently, DSG2 silencing inhibited tumor cell malignancy via suppression of the EGFR-Src-Rac1-PAK1 signaling pathway. Consistent with these findings, a nude mouse xenograft model using H1975 cells demonstrated that DSG2 promoted LUAD cell growth in vivo and increased osimertinib resistance. Collectively, these observations are the first to elucidate a unique role for DSG2 in the development and progression of lung adenocarcinoma via EGFR signaling. Highlights: DSG2 is highly expressed in both LUAD cell lines and tissues. DSG2 promotes proliferation and migration, and increases resistance to the EGFR TKI. Loss of DSG2 results in EGFR translocation into the cytoplasm. DSG2 mediates tumor malignancy via EGFR-Src-Rac1-PAK1 signaling pathway.